Mechanical Ventilation Induces Neutrophil Extracellular Trap Formation. (April 2015) - Yildiz, Christopher; Palaniyar, Nades; Otulakowski, Gail; Khan, Meraj A.; Post, Martin; Kuebler, Wolfgang M.; Tanswell, Keith; Belcastro, Rosetta; Masood, Azhar; Engelberts, Doreen; Kavanagh, Brian P.
Abstract : Background: Mechanical ventilation can injure the lung and induce a proinflammatory state; such ventilator-induced lung injury (VILI) is associated with neutrophil influx. Neutrophils release DNA and granular proteins as cytotoxic neutrophil extracellular traps (NETs). The authors hypothesized that NETs were produced in a VILI model and may contribute to injury. Methods: In a two-hit lipopolysaccharide/VILI mouse model with and without intratracheal deoxyribonuclease (DNase) treatment or blockade of known inducers of NET formation (NETosis), the authors assessed compliance, bronchoalveolar lavage fluid protein, markers of NETs (citrullinated histone-3 and DNA), and markers of inflammation. Results: Although lipopolysaccharide recruited neutrophils to airways, the addition of high tidal mechanical ventilation was required for significant induction of NETs markers ( e.g., bronchoalveolar lavage fluid DNA: 0.4 ± 0.07 µg/ml [mean ± SEM], P < 0.05 vs. all others, n = 10 per group). High tidal volume mechanical ventilation increased airway high-mobility group box 1 protein (0.91 ± 0.138 vs. 0.60 ± 0.095) and interleukin-1β in lipopolysaccharide-treated mice (22.4 ± 0.87 vs. 17.0 ± 0.50 pg/ml, P < 0.001) and tended to increase monocyte chemoattractant protein-1 and interleukin-6. Intratracheal DNase treatment reduced NET markers (bronchoalveolar lavage fluid DNA: 0.23 ± 0.038 vs. 0.88 ± 0.135 µg/ml, P < 0.001; citrullinated histone-3: 443 ± 170 vs. 1, 824 ± 403, P < 0.01, n = 8 to 10) and attenuated the loss of static compliance (0.9 ± 0.14 vs. 1.58 ± 0.17 ml/mmHg, P < 0.01, n = 19 to 20) without significantly impacting other measures of injury. Blockade of high-mobility group box 1 (with glycyrrhizin) or interleukin-1β (with anakinra) did not prevent NETosis or protect against injury. Conclusions: NETosis was induced in VILI, and DNase treatment eliminated NETs. In contrast to experimental transfusion-related acute lung injury, NETs do not play a major pathogenic role in the current model of VILI. Abstract : By creating lung injury in mice using intratracheal lipopolysaccharide and mechanical ventilation, the authors documented that neutrophil extracellular traps were formed when lipopolysaccharide was present during high tidal ventilation and could be treated with deoxyribonuclease I. The treatment cleared the neutrophil extracellular traps and improved lung mechanics, but other measures of lung injury (including increased neutrophil count, increased protein content in lavage fluid, and low oxygenation) persisted, documenting a limited role for the neutrophil extracellular traps in this form of lung injury.Supplemental Digital Content is available in the text.